Differential Subordinations for Certain Meromorphically Multivalent Functions Defined by Dziok-Srivastava Operator - Ying Yang; Yu-Qin Tao; Jin-Lin Liu (Abstract and Applied Analysis)
By making use of the Dziok-Srivastava operator, we introduce a new class of meromorphically multivalent functions. Some inclusion properties of functions belonging to this class are derived.